The Influence of Mass Media Globalisation on the Development of Indonesian Culture - khairul ucok; Alda Aurindya; Jihan Fahira; Paisal Siregar; Aftitah Harahap (Indonesian Journal of Communication and Social, 2024)
The advent of mass media globalisation has exerted a significant impact on Indonesian culture. The objective of this study is to identify and analyse the impact of mass media globalisation on Indonesian culture. The advancement of mass media has become increasingly sophisticated in conjunction with the evolution of communication technology in the contemporary era. It can be seen, therefore, that the development of mass media technology has an impact on the culture and behaviour of Indonesian society. The research method employed is descriptive analysis with a qualitative approach. Data were collected through literature studies based on books and related articles. The results demonstrate that mass media globalisation exerts a multifaceted influence on Indonesian culture. On the one hand, the adoption of global media technology and content has facilitated advances in information access and cross-cultural interaction. However, on the other hand, mass media globalisation also presents challenges to local cultural diversity and national identity.